Correlation Analysis between Different Free Testosterone Index Levels and Clinical Characteristics of Patients with Polycystic Ovary Syndrome - FENG Xiaoling, YIN Wenqing, WANG Ying, HOU Lihui (Zhongguo quanke yixue, 2023)
Background Polycystic ovary syndrome (PCOS) is a common reproductive and metabolic disorder, mainly characterized by hyperandrogenemia. Free testosterone index (FAI) is not only important in the diagnosis of hyperandrogenemia but also closely associated with clinical parameters, such as glucose and lipid metabolism indexes in PCOS patients. Objective To investigate the association between different levels of FAI and the clinical characteristics of PCOS patients. Methods A total of 468 patients with PCOS who were admitted to the gynecology outpatient of the First Affiliated Hospital, Heilongjiang University of Chinese Medicine from October 2019 to June 2021 were included in the retrospective analysis and divided into the low FAI level (LFAI) group (FAI≤2.57, n=156) , medium level FAI (MFAL) group (2.57<FAI≤6.70, n=156) , and high level FAI (HFAI) group (FAI>6.70, n=156) according to the tertile of FAI levels. The general information, sex hormone levels, glucose and lipid metabolism levels, thyroid hormone and uric acid levels of patients in 3 groups were collected. Pearson correlation analysis was used to analyze the correlation between FAI level and clinical parameters of the patients in the three groups. Results In the HFAI group, FAI was positively correlated with body mass (r=0.301) , BMI (r=0.318) , waist circumference (r=0.362) , hip circumference (r=0.307) , WHR (r=0.280) , AND (r=0.407) , glucose at 60 minutes (r=0.298) , glucose at 120 minutes (r=0.279) , glucose at 180 minutes (r=0.281) , FINS (r=0.415) , insulin at 60 minutes (r=0.320) , insulin at 120 minutes (r=0.362) , insulin at 180 minutes (r=0.447) , homeostatic model assessment of insulin resistance (HOMA-IR) (r=0.446) , uric acid (r=0.265) (P<0.05) , and negatively correlated with sex hormone-binding globulin (SHBG) (r=-0.486) (P<0.05) . Conclusion The levels of FAI are closely related to glucose and lipid metabolism indexes in PCOS patients. Therefore, it is crucial to enhance the screening and attention to clinical parameters in PCOS patients with high FAI levels such as glucose and lipid metabolism indexes.